Improving Students’ Activities through the Implementation of Mind Map Script Type (SM2) at SMAN 1 Pulau Punjung - Filmawati Filmawati (AT-TA'LIM, 2015)
This research is motivated from the deficiency of student’s activity in the learning process. The outcome of religious learning process is still low. It shows under 75. By applying cooperative learning model Mind Map Script types, it is expected to be able to enhance students’ motivation through working group learning. This study used a qualitative approach to obtain data and analysis through reflective studies, participatory and collaborative. Mind Map Script is applied to increase learning activity and progress. This study was conducted in SMAN 1 Pulau Punjung with 2 cycles from the observation. Student activities increase from 54% to 75% in the second cycle. Meanwhile, students’ daily test showed an increasing from an average of 65 to 73 in first cycle, and 79 in second cycles. From the first and second cycle of this Classroom Action Research can be concluded that cooperative learning model Mind Map Script types enable to increase students’ activity and learning progress especially in Islamic education studies of grade X student of SMAN 1 PULAU PUNJUNG DHARMASRAYA District.    Key word: activity and learning progress, cooperative model mind map script type (SM2)Copyright © 2015 by Al-Ta'lim All right reserved